PROBLEMS OF O'ZBEK MILLENNIAL FOOD NAMES AND THEIR ENGLISH LANGUAGE (American Journal of Research in Humanities and Social Sciences, 2023)
This article summarizes the problems with the history, types, and translations of Uzbek national dish names. Some of the mistakes and shortcomings made in the process of translating the names of Uzbek national food are shown. Translated artifacts provide examples of food names and diets in dining areas. It also offers solutions to some of the problems associated with the translation of Uzbek national food names from English into English, the advantage of adequate translation in the translation of food, and related methods.